Progressive Enlarging Blind Spot in a Young Asian Lady: A Case Report on Acute Zonal Occult Outer Retinopathy - Alvin Oliver Payus; Ang Wen Jeat; Liew, Constance Sat Lin; Malehah Mohd Noh (2020)
Acute Zonal Occult Outer Retinopathy (AZOOR) is a very rare retinal disease that predominantly affect the Caucasians. It is usually present in a young myopic woman with an acute onset of photopsia and enlarging blind spots. Here, we report a young Asian lady who presented with a typical presentation of AZOOR and later confirmed by electrophysiological test of the retina. She was wrongly diagnosed as retrobulbar optic neuritis due to low index of suspicion for AZOOR among the treating physicians in the hospital. Fortunately, she responded to systemic corticosteroid that was given as a treatment of optic neuritis. AZOOR was only diagnosed later by a visiting European neuro-ophthalmologist in a neighbouring country. The objective of this case report is to remind the reader that the condition exists in Asian population and should be kept as a differential diagnosis in a young lady who presented with progressive visual field defect.